Comparative Outcomes of the Bishop Koop Procedure and Primary Anastomosis in Jejunoileal atresia (Journal of Paediatric Surgeons of Bangladesh, 2025)
Background: Jejunoileal atresia is a common congenital anomaly of the small intestine. The most widely practiced surgical approach is resection of the dilated and hypertrophied proximal bowel followed by primary anastomosis. However, to mitigate the complications associated with primary anastomosis, the Bishop Koop procedure remains a valuable alternative—particularly in developing countries, where access to advanced NICU care and total parenteral nutrition is often limited. Methods: A quasi-experimental study conducted at Dhaka Medical College Hospital between July 2017 and June 2019 including 50 pediatric patients with jejunoileal atresia. Participants were randomly selected to receive either Bishop Koop ileostomy (Group A) or primary anastomosis (Group B). Primary outcomes were-operation time, bowel movement time, time to establish oral feeding, duration of hospital stay, and complication rates. Results: Group A showed significantly shorter less hospital stay duration (8.40 vs 11 days, p=0.004), and fewer complications compared to Group B. The mortality rate in Group A was lower (12% vs. 40%, p=0.024). Anastomotic leakage occurred in 8% of Group A compared to 40% in Group B (p=0.008). In the adjusted bivariate regression analysis model, the likelihood of hospitalization>8 days was determined to be 10 times (95% CI 2.356-46.578) longer in group B than in group A. Conclusion: Bishop Koop ileostomy is associated with improved outcomes, in respect of less hospital stay duration, less complication and lower mortality. These outcomes making it a preferred approach for high-risk neonates with jejunoileal atresia.Journal of Paediatric Surgeons of Bangladesh (2021) Vol. 12 (1 & 2): 3-9